The Combined Reproducing Kernel Method and Taylor Series for Solving Weakly Singular Fredholm Integral Equations - Azizallah Alvandi; Mahmoud Paripour (Institute of Advanced Engineering and Science, 2016)
In this paper, a numerical method is proposed for solving weakly singular Fredholm integral equations in Hilbert reproducing kernel space (RKHS). The Taylor series is used to remove singularity and reproducing kernel function are used as a basis. The effectiveness and stability of the numerical scheme is illustrated through two numerical examples.